Adeus às ilusões: frustração com o jornalismo em alguns romances em português (ou o comércio que envenena, jornalismo que mata e técnica sem saída) - Coutinho, Emildo Pereira (2021)
The objective of this dissertation is to analyze and compare seven novels and a short story in Portuguese (totaling eight texts) that show the representation of frustration regarding the profession of journalist in Brazil in the 20th century. The following texts were chosen and analyzed in chronological order: Recordações do Escrivão Isaías Caminha (Lima Barreto), A Sucessora (Carolina Nabuco), O Inferno é Aqui Mesmo (Luiz Vilela), Abraçado ao Meu Rancor (João Antônio), Adeus, Princesa (Clara Pinto Correia) O Suicida Feliz (Paulo Nogueira), O Ponto da Partida (Fernando Molica) e Jamais Serás um Dhimas Draumann (Emildo Coutinho). As a parameter of criticism, we observe the effects brought on the characters-journalists of these narratives as to their ethical dilemmas and life projects, which point to a final effect of disillusion, frustration and resentment in view of the prospects for acting in this profession. Starting from a point of view related to comparative literature, this work sought to understand the representation of the journalist’s dilemmas with a multidisciplinary reading, involving a critical perspective of communication and technology, in addition to dialogue with the concept of illusion of Freudian psychoanalysis. At the end of the work, we conclude that the characteristic common to the characters-journalists of these narratives is the frustration at being faced with an activity that, although defending the ideals of freedom and clarification, is well integrated with an idea of conformity regarding the consumer society, but at the same time to fight permanently to maintain the ideals of the profession.